Modifying activated carbon with hybrid ligands for enhancing aqueous mercury removal - Zhu, Jianzhong; Deng, Baolin; Yang, John; Gang, Dianchen (Carbon (New York), 2009)
In an effort to enhance mercury (Hg) removal from the aqueous solution, activated carbon (AC) was modified by a combined treatment of nitric acid and thionyl chloride, followed by the reaction with ethylenediamine, to introduce N-, S-, and Cl-containing functional groups. The modified activated carbon (MAC) was characterized by SEM-EDS, FT-IR, XPS, elemental analyzer, and potentiometry. Kinetics and equilibrium isotherms of Hg sorption by MAC were determined in batch experiments. Characterization indicated that additions of the organic–inorganic ligands onto AC surface by treatment were effective, likely through the acyl chloride–carbon reactions. Potentiometric titration showed that the modifications introduced more negative surface charges favoring cation sorption. Kinetics and isotherm studies demonstrated that the Hg sorption by MAC was faster (<30 min) and higher (>200%) than that by AC, suggesting a high affinity of MAC for Hg ions. The sorption by MAC occurred in a wider pH range (4–10 vs. 5–7), and low ionic strength appeared to enhance Hg sorption. The sorption isotherms were best described by Freundlich model, and enhanced Hg sorption by MAC was primarily accomplished by the coordinations of ligand atoms (O, N and S) with Hg ions through the mechanisms of surface complexation, reduction, and ion exchange.